2014
DOI: 10.1007/s10803-014-2078-x
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of GABAA Receptor Protein Subunits α6, β2, δ, ε, γ2, θ, and ρ2 in Superior Frontal Cortex of Subjects with Autism

Abstract: We measured protein and mRNA levels for nine gamma-aminobutyric acid A (GABAA) receptor subunits in three brain regions (cerebellum, superior frontal cortex, and parietal cortex) in subjects with autism versus matched controls. We observed changes in mRNA for a number of GABAA and GABAB subunits and overall reduced protein expression for GABAA receptor alpha 6 (GABRα6), GABAA receptor beta 2 (GABRβ2), GABAA receptor delta (GABRδ), GABAA receptor epsilon (GABRε), GABAA receptor gamma 2 (GABRγ2), GABAA receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 74 publications
5
68
0
Order By: Relevance
“…An E/I imbalance in autism may originate in several ways including increased glutamate activity (25), decreased GABA release (7,8), or decreased numbers of GABA receptors (26). Consistent with the possibility of an E/I imbalance in autism, many of the susceptibility genes may be related to the E/I balance.…”
Section: Significancementioning
confidence: 91%
“…An E/I imbalance in autism may originate in several ways including increased glutamate activity (25), decreased GABA release (7,8), or decreased numbers of GABA receptors (26). Consistent with the possibility of an E/I imbalance in autism, many of the susceptibility genes may be related to the E/I balance.…”
Section: Significancementioning
confidence: 91%
“…The ASD group was all male while seven out of the 11 control group were male. The unequal distribution of sex for the ASD donors reflects the availability of postmortem brain tissue (Casanova et al 2009; Fatemi et al 2014; Fung et al 2014). The postmortem interval was 14.8 h for ASD and 17.1 h for control group.…”
Section: Methodsmentioning
confidence: 99%
“…In ASD, abnormalities have been found in many of the components of this system. For example found reductions in GABA A receptor density in parietal, cerebellar and superior frontal regions in ASD (see also Blatt et al, 2001;Fatemi et al, 2014, Oblak et al, 2011, 2010, and AMPA-type glutamate receptor density was found to be reduced in the cerebellum of individuals with ASD (Purcell, Jeon, Zimmerman, Blue, & Pevsner, 2001). There is also evidence that the synthesis of GABA and glutamate is altered in ASD.…”
Section: Cellular Abnormalitiesmentioning
confidence: 97%